PERAN ORANG TUA DALAM MEMOTIVASI BELAJAR SISWA SELAMA PANDEMI COVID-19 - Irza Majida; Devi Wahyu Ertanti; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
The role of parents can provide motivation for student learning during the COVID-19 pandemic where it is very important for students to increase their enthusiasm for carrying out the teaching and learning process at home. This study aims to determine the role of parents in motivating student learning during the covid-19 pandemic at MI Bustanul Ulum Batu City. This research uses qualitative research with the type of instrumental case study research. Sources of data used in the form of primary data (interviews) and secondary (books and journals). Data collection techniques include observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and conclusions and verification. Checking the validity of the findings using triangulation of data sources. Based on the results of interviews, the role of parents is very important in motivating student learning during the pandemic in order to increase enthusiasm and learning achievement.